Effect of Think-Pair-Share Instructional Strategy on Secondary School Students’ Interest in Chemistry - Ibe, Franklin Nnanna; Ezeliora, Bernadette A.; Okafor, Chinyere F. (EduBase : Journal of Basic Education, 2024)
This study investigated the effect of think-pair-share instructional strategy on secondary school students’ academic interest in Chemistry. It covered the topics; acids, bases and acid-base reactions. Two research questions guided the study and two hypotheses were tested at 0.05 level of significance. The quasi-experimental design was adopted. The population of the study was 5,714 senior secondary school year one (SS1) Chemistry students in Awka Education zone in Anambra State. A sample of 192 SS 1 Chemistry students obtained using stratified and simple random sampling techniques was involved in the study. The instruments for data collection were Chemistry Achievement Test (CAT) and Chemistry Interest Scale (CIS) validated by experts. The reliability of the instruments were established using Kuder-Richardson Formula 20 for CAT which yielded coefficient of internal consistency of 0.81 and Cronbach Alpha for CIS with a reliability coefficient of 0.71. Data were collected by administering the instrument. The data obtained were analyzed using mean and standard deviation to answer the research questions; and analysis of covariance (ANCOVA) to test the hypotheses. The findings of the study revealed that there was significant difference in the mean interest scores of the students taught Chemistry using think-pair-share instructional strategy and those taught using lecture method in favour of think-pair share instructional strategy. Moreso, there was no significant difference in the mean interest scores of male and female students taught Chemistry using think-pair-share instructional strategy. Based on the findings, recommendations were made that workshops and seminars should be organized by school heads to orient Chemistry teachers on how to effectively use think-pair-share instructional strategy in the teaching and learning of Chemistry. The study contributed to knowledge such that it has empirically proved and established that use of TPS improves students' interest in Chemistry surpassing lecture method. The study also revealed empirically that use of TPS in teaching Chemistry enhances male and female students’ interest